2002
DOI: 10.1053/jvet.2002.33589
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Equine Recombinant Growth Hormone on Second Intention Wound Healing in Horses

Abstract: Intramuscular administration of recombinant equine growth hormone (10 microg/kg daily for 7 days, then 20 microg/kg daily for 49 days) does not appear to have any beneficial clinical effect on healing of equine limb wounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 24 publications
(98 reference statements)
0
23
0
1
Order By: Relevance
“…5,10 Digital photographs of the wounds were obtained on days 1, 7, 14, 21, 28, 35, 42 and 49 after wound creation and wounds were measured using image analysis software (Scion Image, Scion Corporation, USA) as previously described. 12,13,27 A 2.5 × 2.5 cm template (6.25 cm 2 ) was placed next to the wound as a standard reference. The area of the wound (cm 2 ) was measured three times and the average calculated to produce a single measure for each wound on each day.…”
Section: Wound Measurementsmentioning
confidence: 99%
“…5,10 Digital photographs of the wounds were obtained on days 1, 7, 14, 21, 28, 35, 42 and 49 after wound creation and wounds were measured using image analysis software (Scion Image, Scion Corporation, USA) as previously described. 12,13,27 A 2.5 × 2.5 cm template (6.25 cm 2 ) was placed next to the wound as a standard reference. The area of the wound (cm 2 ) was measured three times and the average calculated to produce a single measure for each wound on each day.…”
Section: Wound Measurementsmentioning
confidence: 99%
“…Most experimental studies of equine distal limb wound healing using surgical models have been performed on forelimbs. 43 The results of the present study suggested that in clean uncontaminated wounds of the distal limb in horses UMF20 is superior to both commercial food-grade multifloral honey and UMF5 as a topical treatment to enhance healing. 43 That study showed that hindlimb wounds healed significantly slower than forelimb wounds, but the pattern of healing is similar, with wounds initially retracting, followed by a period of consistent and steady contraction.…”
Section: Discussionmentioning
confidence: 57%
“…[28][29][30] Although UMF20 reduced the overall wound healing time compared with GH and the control, the healing times for all treatment groups were longer than those observed in previous studies of secondintention healing in forelimb wounds. 43 That study showed that hindlimb wounds healed significantly slower than forelimb wounds, but the pattern of healing is similar, with wounds initially retracting, followed by a period of consistent and steady contraction. [1][2][3][4][5][6][7][28][29][30][39][40][41][42] However, the prolonged healing times in this study are consistent with the results of the only other study to investigate distal limb wound healing in equine hindlimbs.…”
Section: Discussionmentioning
confidence: 99%
“…Recombinant equine growth hormone (reGH) has recently been evaluated for various applications in the horse (Malinowski et al 1997;McKeever et al 1998;Dart et al 2002). When administered s y s t e m i c a l l y, reGH increased plasma concentrations of IGF-1 and improved body condition in aged mares (Malinowski et al 1 9 9 7 ;McKeever et al 1998).…”
Section: Introductionmentioning
confidence: 99%